TRANSAKSI SHORT SELLING DITINJAU DARI PERLINDUNGAN INVESTOR DALAM HUKUM PASAR MODAL INDONESIA - sendi sanjaya; Ifat Hanifah; Rahmah Meladiah; Feriadi (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2022)
Short selling transaction is one of the securities exchage transactions. Short selling transactions are dealt with separately by Bapepam-LK No V.D6 and Exchae Rule Bumber II-H. Issues raised in this paper is how the legal protection of investors. Based on the research result obtained : First, that transaction of selling is a legitimate transaction in Indonesia although often cause failure to deliver and other potential losses. Second, that the existence of new facilities such as C-BEST in general can prevent violations in the capital market, so that the risk of loss can diminalisir, although still requiring special system governing short selling transactions specificially.